2004
DOI: 10.1111/j.1349-7006.2004.tb03173.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation of cigarette smoking and alcohol use to colorectal adenomas by subsite: The self‐defense forces health study

Abstract: While smoking has consistently been shown to be related to increased risk of colorectal adenomas, few studies have addressed the association between smoking and site-specific colorectal adenomas. The reported association between alcohol use and colorectal adenomas has been inconsistent. We evaluated risks of adenomas at the proximal colon, distal colon, and rectum in relation to cigarette smoking and alcohol use, and their interaction. Subjects were 754 cases with histologically proven colorectal adenomas and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 35 publications
4
35
1
1
Order By: Relevance
“…Similar results in a Tunisian study where CRC adenocarcinoma was well differentiated in 46% of cases, moderately differentiated in 33.3% of cases and undifferentiated in 11.3% of cases [55]. Our series and the Moroccan series report the same results [47,56,57].…”
Section: Discussion:-supporting
confidence: 79%
See 1 more Smart Citation
“…Similar results in a Tunisian study where CRC adenocarcinoma was well differentiated in 46% of cases, moderately differentiated in 33.3% of cases and undifferentiated in 11.3% of cases [55]. Our series and the Moroccan series report the same results [47,56,57].…”
Section: Discussion:-supporting
confidence: 79%
“…It appears in a complicated form in 30 to 50% of cases (occlusion, perforation, internal fistula) [19]. Rectal involvement is dominated by the involvement of the lower rectum [47]. The most common histological form of CRC (approximately 96%) is adenocarcinoma [48].…”
Section: Discussion:-mentioning
confidence: 99%
“…Epidemiologic studies across different continents have consistently reported that cigarette smoking is a strong adenoma risk factor (1)(2)(3)(4)(5)(6)(7)(8)(9). The strength of the associations and the overall consistency of the results across different populations suggest that smoking is likely to be causal.…”
Section: Introductionmentioning
confidence: 79%
“…Details of the health examination and a lifestyle survey have been described elsewhere. (22,23) In addition to blood samples for routine use in the health examination, a sample of 7 mL fasting venous blood was obtained for the purpose of medical research with written informed consent. The study was approved by the ethical committee of Kyushu University.…”
Section: Subjectsmentioning
confidence: 99%